ARTIFICIAL INTELLIGENCE IN COMPUTER ENGINEERING: PSYCHOLOGICAL APPROACHES TO UNDERSTANDING HUMAN BEHAVIOR - Shreyasa Rani Dubey; Diwakar Pandey (Bulletin of Engineering Science, Technology and Industry, 2024)
The integration of Artificial Intelligence (AI) in computer engineering has significantly advanced the field's ability to understand and predict human behavior. This research article explores the intersection of AI and psychological approaches, examining how computational models can simulate cognitive processes and emotional responses. By leveraging machine learning algorithms and neural networks, the study demonstrates how AI systems can analyze vast datasets to identify patterns in human behavior, providing insights into decision-making, social interactions, and mental health. The article also discusses the ethical implications of AI-driven behavioral analysis and the potential for enhancing human-computer interactions. Through a comprehensive review of current methodologies and case studies, this research highlights the transformative impact of AI on understanding human behavior and proposes future directions for integrating psychological theories with AI technologies to further enhance the accuracy and applicability of behavioral predictions in computer engineering.